PENGEMBANGAN BAHAN AJAR BERBENTUK MEDIA POSTER PADA MATERI CERITA - Inti Khobatsaniyah; Mustofa Mustofa; Anisa Ulfah (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to develop teaching materials in the form of poster media in learning Indonesian fable story material by measuring the validity, practicality and effectiveness of the poster media. This research was tested at MTs Al Khoiriyah 2 Mulyorejo Dalegan Panceng Gresik, the subject of the research was class VII stud ents with 10 students. This study uses a development model as suggested by Thiagarajan and Sammel (1974). This model consists of four stages of development, namely define, design, development, and dissemination. The instruments used in this study were a material expert validation questionnaire, design expert validation, practicality questionnaire, student response questionnaire and pretest posttest questions to determine the effectiveness of teaching materials in the form of poster media. The results show that: the development of poster media products has gone through the assessment stage by material expert lecturers, design expert lecturers, practitioners (teachers), field trials (students). The overall rating average got a final score of 89.6% with a very decent category. Based on these results, the teaching materials in the form of poster media that have been developed are feasible to use.